Beckett at reading. Catalogue of the Beckett manuscript collection at the University of Reading. s.l., Whiteknights Press and the Beckett International Foundation, 1998. - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras., 1999)
Mary Bryden. Julian Garforth and Peter Mills. Beckett at reading. Catalogue of the Beckett manuscript collection at the University of Reading. s.l., Whiteknights Press and the Beckett International Foundation, 1998.Reseña por Lucas Margarit.
Fil: Margarit, Lucas. Universidad de Buenos Aires. Facultad de Filosofía y Letras; Argentina.
Keywords: BECKETT, SAMUEL; MANUSCRITOS; CATÁLOGOS; ARCHIVO BECKETT; RESEÑAS BIBLIOGRÁFICAS